Effectiveness of occupational health intervention programme on work place environmental risks and stress management among nurses in south-west Nigeria (2006)
"The nurse’s role has long been regarded as stress filled based on the physical labour human suffering, work hours, staffing and interpersonal relationships that are central to the work nurses do. Occupational stress is thus, a recognized problem among health care workers in general. Nursing has therefore been identified as an occupation that has high level of risks and stress in the work place environment. Therefore the study investigated the effects of occupational health intervention programme on environmental risks and stress management of staff nurses in South-west Nigeria. A pretest, posttest, control group, quasi-experimental research design was adopted. Two hundred and twenty five (225) respondents were selected for the study. One hundred and twelve (112) respondents were used as experimental group while one hundred and thirteen (113) respondents were used as control group. Fish bowl method was used for grouping the participants into experimental and control groups respectively. A self-developed questionnaire tagged ‘Occupational Health Intervention Programme, Environmental Risks and Stress Management Questionnaire OHIPERSMQ’ with a reliability coefficient of 0.88 was used. The experimentation lasted 8 weeks. Analysis was done using ANCOVA and Multiple Classification Analysis. Hypotheses were tested at 0.05 alpha level. Findings revealed that occupational health intervention programme has significant effect on risk management knowledge of staff nurses. The experimental group had mean = 4.44, better than the control group that had mean = 2.92. Also, occupational health intervention programme had significant effect on stress management knowledge of nurses with experimental group mean = 7.78, better than the control group mean = 2.36. Based on these findings, it was recommended that medical social workers should ensure that nurses participate in educational training in skills associated with risk reduction, stress reduction and safety promotion so as to guarantee their wellbeing and good job performance."